تثبيط المخاض الباكر دراسة مقارنة بين استخدام النيفيدبين والسالبوتامول في تثبيط المخاض الباكر والآثار الجانبية لهما على الأم وحديث الولادة - عبد الرحمن, أحمد; الدالي, عصام; يونس, شادي (Latakia University Journal -Medical Sciences Series, 2019)
تناولت الدراسة ل(102) امرأة حامل بأعمار حملية أقل من 34 أسبوع حملي لديهن تقلصات رحمية ( تقلصتين رحميتين عرضيتين على الأقل خلال 10 دقائق وتستمر لأكثر من 60 دقيقة بعد القبول في المشفى ). بعد تصنيف الحوامل بشكل عشوائي لاختيار الدواء المستخدم في تثبيط المخاض الباكر إما السالبوتامول وريدياً أو النيفيدبين فمويا ً، ( 55 ) حامل شكلن مجموعة النيفيدبين و( 47 ) حامل شكلن مجموعة السالبوتامول. تمّ إجراء مقارنة بين المجموعتين بالعديد من المتغيرات والتي تلعب دور مهم في إمراضية المخاض الباكر. إن الولادة في مجموعة النيفيدبين تمّ تأخيرها لما بعد 48 ساعة،7 أيام وحتى 34 أسبوع حملي في 33 (60%)، 26 (47%)، 21 (38%) حالة على التوالي، مقارنةً مع 31 (66%)، 21 (45%)، 11 (23%) للنساء في مجموعة السالبوتامول. لم يشاهد فرق إحصائي مهم بين المجموعتين. إن الآثار الجانبية الوالدية كانت بشكل واضح أقل شيوعا ًفي مجموعة النيفيدبين من مجموعة السالبوتامول، إن النتائج عند حديثي الولادة كانت متقاربة في كلا المجموعتين. وبالنتيجة يبدو أن النيفيدبين متساو الفعالية مع السالبوتامول في تثبيط المخاض الباكر ولكنه يترافق مع آثار جانبية أقل. A randomized selection of 102 pregnant women with gestational ages under 34 weeks and had uterine contractions (premature labour) with at lest two contractions in 10 minutes for at least 60 minutes after admission. After stratification, women were randomly assigned to receive either Salbutamol intravenously or Nifedipine orally. Fifty-five women were randomized to the Nifedipine group and 47 to the Salbutamol group. As expected, both groups were compared in terms of several entry variables that play an important role in premature labour. Delivery of women in the Nifedipine group was delayed for 48 h, 7 days, and until 34 weeks gestation in 33 (60%), 26 (47%) and 21(38%) cases, respectively, compared with 31 (66%), 21(45%) and 11(23%) women in the Salbutamol group (no significant difference). Maternal side effects were significantly less common in the Nifedipine group than those in the Salbutamol group. Neonatal outcome was similar in the two groups. In conclusion, Nifedipine seems to be as effective as Salbutamol in the treatment of premature labour and is associated with less frequent side effects.